First recorded case of female Brown bear (Ursus arctos: Ursidae) with five second year cubs - Sedash, Gleb A.; Matiukhina, Dina S.; Sonin, Petr L.; Blidchenko, Ekaterina Yu; Storozhuk, Victor B. (Nature Conservation Research: Заповедная наука, 2018)
We report the first case of a super-large brown bear (Ursus arctos) litter surviving until the second year of life. In the Land of the Leopard National Park, using camera traps, we recorded a female with five cubs two times – in March and in December 2017. Litters with more than four cubs are extremely rare for brown bears, and are known for newborn cubs only. We report the first documented evidence of a five-cub litter, which are very close to surviving through the first two years of their life while bear cub mortality is extremely high.